Influence of Leaf Extract of Lantana camara Integrated with Maize-based Coating on the Quality of Fresh Talinum triangulare and Telfairia occidentalis Leaves - Adeogun, Oluwagbenga Oluwasola; Ebabhi, Abosede Margaret; Adongbede, Erute Magdalene; Oluwa, Omoteso Karfeel; Adekunle, Adedotun Adeyinka (Universitas Sebelas Maret, 2023)
Fresh Talinum triangulare and Telfairia occidentalis leaves have a short shelf life; therefore, there is a need to enhance their shelf life using natural antimicrobials to maintain their freshness. The effect of an ethanolic extract of Lantana camara leaf (10% w/v) integrated with a maize-based edible coating on fresh T. triangulare and T. occidentalis leaves was studied. Fresh T. triangulare and T. occidentalis leaves were evaluated for quality (pH, total carotenoid content, ascorbic acid, total phenolic content, fungal load, antioxidant activity, total soluble solids and browning potential) using a centered second-order polynomial (quadratic) model over a 9-day period. The pH values, browning potential, total soluble solids, and fungal loads of T. triangulare and T. occidentalis treated with the ethanolic leaf extract of L. camara integrated with maize-based coating had higher values than those of T. triangulare and T. occidentalis without treatment. Meanwhile, the total carotenoid content, ascorbic acid, total phenolic acid, and total antioxidant capacity of T. triangulare and T. occidentalis treated with the ethanolic leaf extract of L. camara integrated with maize-based coating had reduced values compared to T. triangulare and T. occidentalis without treatment. The disparity in the quality parameter values indicates bioactivity in L. camara integrated with a maize-based coating. This study shows that the integration of the ethanolic extract of the leaf of L. camara with the maize-based coating could be used as a biopreservation agent to improve the shelf life of T. triangulare and T. occidentalis.